Crystallographic studies of fish hemoglobins - Plínio Delatorre (Eclética Química, 2000)
The present work reports our succesfull experienceconcerning crystallization of four fish hemoglobins from three Brazilianspecies of Teleosts: Liposarcus anisitsi, Brycon cephalus and Piaractusmesopotamicus. The data shown here is part of a systematic functionaland structural study of fish hemoglobins with the aim of betterunderstanding the outstanding range of functional and structuralproperties exhibited by these proteins. We also present a reducedsparse-matrix method for crystallization of fish hemoglobins, which canreduce the amount of hemoglobin initially used in the crystallizationexperiments.